Herding Behaviors in ASEAN Stock Markets - Yao, Jian; Tangjitprom, Nopphon (Journal of Applied Economics and Management Strategy, 2019)
ABSTRACT This paper aims to use comprehensive evidence to test the herding behaviors existing in 6 ASEAN stock markets, including Indonesia, Malaysia, the Philippines, Singapore, Thailand, and Vietnam. The paper used a survivor-bias-free dataset of daily stock returns during the period January 1, 2009 to June 30, 2016 to measure the results. The empirical results from the 6 ASEAN stock markets showed that herding behavior has existed only in Vietnam, and Vietnam own significant herding behavior during different asymmetric market conditions. We also found evidence to show the significant role of U.S. return dispersions in the ASEAN stock market; however, the U.S. stock market cannot affect the herding formation of each ASEAN stock market. Keywords: Herding Behavior, Cross-sectional Absolute Deviation, ASEAN Stock Markets